Bridging Perspectives of Customer Value Proposition and Customer Perceived Value of Intercity Non-Bus Transportation Service in Indonesia - Hadiansah, Ihsan; Nugraha, Rendika; Santoso, Adhi Setyo; Purwanegara, Mustika Sufiati (UI Scholars Hub, 2018)
Research Aims - The study aim is to explore value proposition creation from the perspectives of non-bus transportation services and to investigate the factors in customer perceived value, especially functional value (operations, facilities, professionalism, and price), that influence purchase intention from customers’ perspectives. Design/methodology/approach - This mixed methods study used personal interviews, participant observation, and a survey to collect the data. Then, we conducted exploratory case study by using organisational level logic model as a qualitative analysis technique. Finally, we used regression for hypothesis testing of the quantitative section. Research Findings - The results indicated that non-bus transportation services should give extra efforts to build great value propositions to meet customer needs. The interview and participant observation results on non-bus transportation service providers’ perspectives showed that that two providers studied have different strategies to create strong value propositions. The survey results on customers’ perspectives showed that all aspects of functional value (operations, facilities, professionalism, and price) significantly influence purchase intention. Thus, those two perspectives do not completely align. Theoretical Contribution/Originality - The integrated framework of customer value proposition created by firms and customer perceived value, which was empirically tested in this study, showed that superior value proposition can be achieved where there is a feedback loop between these two perspectives. Managerial Implications in the Southeast Asian context - Managers have to consider not only the individual aspects of price competitiveness and comfort of services as value propositions but also the integration of facilities and professionalism to build perceived value through value propositions in intercity non-bus transportation services in Southeast Asian contexts. Research limitations and implications - This study had only two variables (functional value and purchase intentions). Functional value had four sub-variables (operations, facilities, professionalism, and price) as independent variables. Other variables could influence purchase intention for non-bus transportation service providers.